Macroeconomic Risk Management Against Natural Disasters Analysis focussed on governments in developing countries - Hochrainer, Stefan; SpringerLink (Online service) (Wiesbaden : DUV, 2006)
Natural disasters cause considerable economic damage. While developed countries usually are able to cope with the impacts of natural hazards, developing countries are faced with severe consequences for their resources. In order to prevent long-term macroeconomic repercussions, governments need a comprehensive disaster risk management strategy. Stefan Hochrainer develops a catastrophe risk management model. It illustrates which trade-offs and choices a country must make in managing economic risks due to natural disasters. Budgetary resources are allocated to pre-disaster risk management strategies to reduce the probability of financing gaps. The framework and model approach allows cross country comparisons as well as the assessment of financial vulnerability, macroeconomic risk, and risk management strategies. Three case studies demonstrate its flexibility and coherent approach.
Natural disaster risk -- Economic impacts - Statistical analysis -- Natural disaster risk management measures -- Financial resilience of the public sector -- Catastrophe modeling and simulation -- Case Studies -- Conclusion and future work.
Keywords: Finance; Operations research; Decision making; Finance; Finance, general; Operation Research/Decision Theory; Electronic books